PRIVATE LIFE IN DAGESTANI AULS THROUGH CONTEMPORARY ACCOUNTS (LATE 19TH – EARLY 20TH CENTURY) - Dalgat, El'mira Murtuzalievna; Navruzov, Amir Ramazanovic (History, Archeology and Ethnography of the Caucasus, 2024)
This study examines private life within Dagestani auls as perceived by contemporary observers. Family life, often considered a highly conservative domain, exhibits relative resilience to broader societal and state influences. This research aims to explore specific aspects of private life, namely family structures and the position of women within them, through the perspectives of Dagestani villagers and Russian visitors during the second half of the 19th and early 20th centuries. The analysis incorporates works by Abdul Omarov, Maksud Alikhanov, and Karanailov, as well as those of Bashir Dalgat and Said Gabiev, representatives of the emergent secular democratic intelligentsia. Furthermore, it considers the views of Muslim intellectual figures such as Ali Kayayev and Abusufyan Akayev regarding women’s familial roles. Russian authors who documented their experiences in Dagestan, including N. Lvov, N. I. Voronov, N. Dubrovin, and A. T. Vasiliev, among others, also feature in this study. Employing descriptive, comparative, and historical methodologies, the research compares and contrasts indigenous and Russian perspectives on family life in Dagestani villages. Source materials include memoirs published in the “Collections of Information about the Caucasian Mountaineers”, alongside articles from journals such as “Etnograficheskoe Obozrenie” and “Zhivaya Starina”, and the newspaper “Dzharidat Dagestan”. An examination of these perspectives on family life reveals that they have both commonalities and differences. Indigenous authors generally maintained that traditional customs – adats – significantly shaped familial and social dynamics within the highlands, defining the rights and responsibilities of spouses. Some, aligned with liberal democratic ideals, perceived women’s position as comparatively disadvantaged. Reform-minded individuals advocated for gender equality within the family unit. Conversely, Russian authors tended to emphasize the perceived oppression and disempowerment of women in daily life within the highland communities. This research suggests that despite the inherent conservatism of this domain of social life, incremental positive shifts were occurring in family structures, arguably influenced by Dagestan’s incorporation into the Russian Empire.
Keywords: Dagestan; private life; family and family life; gender equality in marriage; local and Russian authors; transformation